An IR-UWB Transmitter using Pulse Injection - Nontapat Channarong; Kritsapon Leelavattananon (My University, 2019)
This work presents a new pulse-shaping technique for an impulse-radio ultra-wideband (IR-UWB) transmitter which is intended for RFID tags and wireless sensor applications. The proposed pulse is derived from a rectangular pulse with its side-band energy suppressed in order to satisfy the FCC UWB regulation, in particular at low frequency band (3.1 - 4.8 GHz). To verify its effectiveness, the new pulse generator was designed in a 180-µm CMOS process. The simulation results indicate that the spectrum of the transmitted pulse can be fitted within the FCC UWB spectral mask. The total circuit consumes 926 µW at a 10 MHz pulse repetitive frequency (PRF).
Keywords: Impulse Radio; Impulse generator; Radio Frequency Integrated Circuit Design